Improved model of streamer propagation in liquid dielectrics. Issue 8 (1st July 2019) - Lehouidj, B.; Hadji, Y.; Sahra, S.; Nacer, A.; Moulai, H.
Abstract : Breakdown and pre‐breakdown cause extensive damage in dielectric oils used in power systems subjected to high voltages. Consequently, several research works are devoted to these phenomena. Related investigations are made very difficult by the numerous influencing parameters and the large number of characteristics of these phenomena. The main goal of the present work was to establish a new electrical model that describes the propagation of streamers in liquid dielectrics for a point‐plane configuration subjected to high‐voltage fields. The novelty consists in the presence of an inductance in the equivalent electrical circuit, which represents the dielectric during the partial discharges characterized by fast variations of current. Criticisms were first made concerning previous electrical models that show some disadvantages. The developed model consists of a series RLC circuit whose element values change during propagation. In particular, the value of the resistance decreases in anticipation of breakdown. The simulation of the developed model gave satisfactory results, similar to experimental ones. For instance, the influence of electrical and geometrical parameters on the current pulses amplitude as well as on the streamers propagation velocity and the quantity of charge and the energy injected were studied. Good agreement was also obtained between the obtained results and experimental ones, which reinforces the validity of the model.